2021
DOI: 10.3390/en14040880
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Aerodynamic Performance of Different Forms of Adaptive Blades for Vertical Axis Wind Turbines

Abstract: The wind energy exploitation technique has been developed very quickly in recent years. The vertical axis wind turbine is a hot research domain due to several advantages: low noise, flexible for installation, ease of maintenance, great safety and credibility, etc. The aerodynamic performances of different forms of airfoils including an active deformation airfoil and a fluid-solid coupling passive airfoil with two-dimensional (2D) and three-dimensional (3D) cases have been investigated numerically in this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In recent years, various techniques for deflector installation and modified designs have been reported [22]. Many of these designs have been reported with validated simulations and have contributed to turbine blade wind flow improvements.…”
Section: Increased Structural Complexitymentioning
confidence: 99%
“…In recent years, various techniques for deflector installation and modified designs have been reported [22]. Many of these designs have been reported with validated simulations and have contributed to turbine blade wind flow improvements.…”
Section: Increased Structural Complexitymentioning
confidence: 99%
“…In their study, using active hinged flaps, there was double the fatigue reduction potential compared with the original blade, while the increment in AEP was approximately 1% 18 . It has also been shown that in vertical axis wind turbines, the use of morphing blades increases the pressure coefficient and delays the separation of the flow 19,20 . McWilliam et al used a morphing flap on a constant length in their aeroelastic optimization of the 10‐MW wind turbine blade and investigated its effect on each speed compared with the baseline blade.…”
Section: Introductionmentioning
confidence: 99%
“…18 It has also been shown that in vertical axis wind turbines, the use of morphing blades increases the pressure coefficient and delays the separation of the flow. 19,20 McWilliam et al used a morphing flap on a constant length in their aeroelastic optimization of the 10-MW wind turbine blade and investigated its effect on each speed compared with the baseline blade. The flap they added to the reference blade increased the AEP by 0.51%, while the contribution of aeroelastic optimization was above 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the angle of attack allows VAWTs to start operating earlier and achieve their cut-in speed (the minimum wind speed required for the turbine to start generating power) more effectively; -Performance at Different Wind Speeds-Wind speed is not constant, and it varies with height and atmospheric conditions. VAWTs experience changing wind speeds as the rotor rotates, which affects the angle of attack [17]. By actively controlling the angle, the turbine can optimize power production by adjusting to the wind speed changes.…”
Section: Introductionmentioning
confidence: 99%